Major areas of interest of artificial intelligence research applied to health care administrative data: a scoping review - Bukhtiyarova, Olga; Abderrazak, Amna; Chiu, Yohann; Sparano, Stephanie; Simard, Marc; Sirois, Caroline (Frontiers in Pharmacology, 2022)
Introduction: The ongoing collection of large medical data has created conditions for application of artificial intelligence (AI) in research. This scoping review aimed to identify major areas of interest of published studies related to application of AI to medico-administrative data. Methods: The search was performed in seven databases: Medline, Embase, CINAHL, Web of science, IEEE, ICM digital library, and Compendex. We included articles published between January 2001 and March 2021, that described original research in AI applied to medical diagnostics, pharmacotherapy, and health outcomes data. We screened the full text content and used natural language processing to automatically extract health areas of interest, principal AI methods, and names of medications mentioned in the articles. Results: Out of 14,864 articles, 343 were included. We determined ten areas of interest, the most common being health diagnostics or outcome prediction (32%); representation of clinical data (22%); and adverse drug effects, drug-drug interactions, and medication cascades (15%). Less attention has been devoted to health of socio-demographic groups (3%); solving problems of missing data (2.6%); health effects of polypharmacy (1%); and reinforcement learning (1%). The most common AI methods were decision trees, cluster analysis, random forests, and support vector machines. Medications most frequently mentioned included insulin, metformin, vitamins, acetaminophen, and heparin. Conclusions: The scoping review revealed the potential of AI application to health-related studies. However, several areas of interest in pharmacoepidemiology are sparsely reported, and the lack of details in studies related to pharmacotherapy suggests that AI could be used more optimally in pharmacoepidemiologic research.